Pembuatan Sirup Glukosa Dari Tepung Sagu Yang Dihidrolisis Dengan Asam Klorida - E, Sutanto; Yusnimar, Yusnimar; E, Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Sago is one of carbohydrates potential resource for foods and raw materials in industries. Sago can be treated to a glucose syrup by using HCl 0,5N as a catalyst. The purpose of this research is make glucose syrup with the process of hydrolysis of sago flour and determining the influence of temperature, volume the addition of acid and hydrolysis time on reducing sugar concentration of syrup produced. In order to get the highest of glucose concentration in these syrup, in this research sago hydrolysis process have been done under variation of the volume acid (10, 15 and 20 ml), the hydrolysis temperatures (105, 115 and 125 oC) and the hydrolysis time (15, 30 and 45 minutes). The glucose syrup were analyzed, such as water content by SNI 08-7070-2005 and glucose content by the Nelson-Somogyi method. Based on the result, the highest of glucose content in this syrup is 67.7% under condition the addition of 0.5 N HCl volume by 15 ml, hydrolysis time 30 minutes and temperature of 125 oC. The resulting glucose syrup meets the standard based on SNI 01-2978-1992 namely glucose concentration of more than 30% and a water content of less than 20%. Keywords: Glucose, Glucose Syrup, Hydrolysis, Sago